Impaired Dopamine Release and Latent Learning in Alzheimer's Disease Model Zebrafish - Jarosova, Romana; Niyangoda, Sayuri S; Hettiarachchi, Piyanka; Johnson, Michael A (ACS chemical neuroscience, 2022)
Alzheimer's disease (AD) is a progressive, fatal, neurodegenerative disorder for which only treatments of limited efficacy are available. Despite early mentions of dementia in the ancient literature and the first patient diagnosed in 1906, the underlying causes of AD are not well understood. This study examined the possible role of dopamine, a neurotransmitter that is involved in cognitive and motor function, in AD. We treated adult zebrafish (Danio rerio) with okadaic acid (OKA) to model AD and assessed the resulting behavioral and neurochemical changes. We then employed a latent learning paradigm to assess cognitive and motor function followed by neurochemical analysis with fast-scan cyclic voltammetry (FSCV) at carbon fiber microelectrodes to measure the electrically stimulated dopamine release. The behavioral assay showed that OKA treatment caused fish to have lower motivation to reach the goal chamber, resulting in impeded learning and decreased locomotor activity compared to controls. Our voltammetric measurements revealed that the peak dopamine overflow in OKA-treated fish was about one-third of that measured in controls. These findings highlight the profound neurochemical changes that may occur in AD. Furthermore, they demonstrate that applying the latent learning paradigm and FSCV to zebrafish is a promising tool for future neurochemical studies and may be useful for screening drugs for the treatment of AD.
Keywords: Microelectrodes; mikroelektrody; kyselina okadaová; dopamin; Animals; Zebrafish; Dopamine; karbonové vlákno; Alzheimerova nemoc; Carbon Fiber; Okadaic Acid; neurotransmiterové látky; Alzheimer Disease; dánio pruhované; zvířata; Neurotransmitter Agents